Continuation of the genetic divergence of ecological speciation by spatial environmental heterogeneity in island endemic plants - Bing-Hong Huang (Nature Portfolio, 2017)
Abstract Divergent selection plays a critical role not only as a speciation driver but also in maintaining post-speciation divergence. In the absence of direct evidence, ancestral interspecific gene flow between incipient species can reflect ancient selective pressure for ecological speciation. In the present study, two late-Pleistocene diverged species endemic to Taiwan, Scutellaria playfairii and S. tashiroi, were spatially and ecologically partitioned with partial overlap. Multilocus genome-scan analyses and in silico evaluation revealed ancestral interspecific gene flow but distinct genetic compositions, implying that adaptive divergence contributed to their speciation. Ecological niche modeling and principal component analysis suggested incomplete divergent niches between the two species; the species distribution is therefore consistent with Hutchinson’s metaphor of multidimensional hypervolume niches rather than attributable to a single factor. Constraint ordination analysis supported this inference of a combination of variables explaining the genetic structure. The rare occurrence of hybrids in the sympatric population suggested hybrid breakdown, providing further evidence of divergent selection blocking gene flow. The correlation of environmental variables with integrated genetic components demonstrated that environmental heterogeneity maintains the species and population differentiation. This study highlights the importance of environmental heterogeneity and divergent selection for the rapid speciation and recent diversification of island plants.